Technical Note: Combining undisturbed soil monoliths for hydrological indoor experiments - D. Ramler; P. Strauss (Hydrology and Earth System Sciences, 2023)
An important decision in soil hydrological research is whether to conduct experiments outdoors or indoors. Both approaches have their advantages and trade-offs. Using undisturbed soil monoliths combines some of the advantages of outdoor and indoor experiments; however, there are often size limitations. Acquiring large monoliths necessitates heavy machinery, which is time-, cost-, and labor-intensive. Small- to medium-sized soil blocks, however, can be obtained using less demanding methods. A promising approach is the combination of smaller blocks to form a single large monolith, thereby optimizing cost and labor efficiency as well as representativity and upscaling potential. To this end, we compared the runoff properties of medium-sized (1×0.5×0.35<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="67pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="eaca02e00394b85867bc200e9170f3dd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="hess-27-1745-2023-ie00001.svg" width="67pt" height="10pt" src="hess-27-1745-2023-ie00001.png"/></svg:svg> m) grassland soil monoliths cut in half and recombined with uncut blocks. We conducted artificial runoff experiments and analyzed the chemical composition and amount of outflow from four flow pathways (surface runoff, subsurface interflow, percolating water, lateral flow). Furthermore, we studied surface runoff velocity parameters using a salt tracer. Our results suggest that the effects of the recombination procedure are negligible compared to the variation in the data caused by the inherent soil heterogeneity. We propose that the benefits of combining soil monoliths outweigh the potential disadvantages.